2015
DOI: 10.23937/2378-3419/2/1/1013
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Specific Promoter Methylation Status in Hormone-Receptor-Positive Breast Cancer Associates with Postmenopausal Body Size and Recreational Physical Activity

Abstract: Introduction Breast cancer, the leading cancer diagnosis among American women, is positively associated with postmenopausal obesity and little or no recreational physical activity (RPA). However, the underlying mechanisms of these associations remain unresolved. Aberrant changes in DNA methylation may represent an early event in carcinogenesis, but few studies have investigated associations between obesity/RPA and gene methylation, particularly in postmenopausal breast tumors where these lifestyle factors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
(60 reference statements)
0
14
2
Order By: Relevance
“…9 BC progression is most likely a multifactorial condition involving complex interactions among genetic/epigenetic and estrogen-related and inflammation-related factors. [12][13][14][15][16] Global and tumor gene-specific aberrant Cancer November 1, 2019 DNA methylation have been associated with BC prognosis in previous reports, including our own. Epigenetic modifications involve changes in gene function but do not entail a change in DNA sequence.…”
Section: Introductionmentioning
confidence: 50%
See 3 more Smart Citations
“…9 BC progression is most likely a multifactorial condition involving complex interactions among genetic/epigenetic and estrogen-related and inflammation-related factors. [12][13][14][15][16] Global and tumor gene-specific aberrant Cancer November 1, 2019 DNA methylation have been associated with BC prognosis in previous reports, including our own. Epigenetic modifications involve changes in gene function but do not entail a change in DNA sequence.…”
Section: Introductionmentioning
confidence: 50%
“…10 Methylation may occur during embryogenesis, is heritable by somatic cells after cell division, 11 but also can be modified during the life course under environmental stimulation and lifestyle modulation. [12][13][14][15][16] Global and tumor gene-specific aberrant Cancer November 1, 2019 DNA methylation have been associated with BC prognosis in previous reports, including our own. [17][18][19] Aberrant DNA methylation may lead to whole-genomic instability and altered gene transcription, 15 which may further induce increased mutation rates of key genes (including COX-2) upon which that aspirin acts.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Increased BMI has also shown a positive association with hypermethylation of both RASSF1A and BRCA1 in surgically excised breast tumours ( n = 120; Naushad et al, ). Studies have also identified that obesity was associated with hypermethylation of hairpin‐induced 1 ( HIN1 ) in post‐menopausal breast tumour tissue ( n = 532) from the Long Island BC Study Project (McCullough et al, ). The HIN1 gene encodes a protein that is a negative regulator of both cell growth and invasion (Krop, Parker, Qimron, Porter, & Polyak, ).…”
Section: Dietary Fat Obesity and Targeting Of Dna Methylation In Bcmentioning
confidence: 99%